Conservation agriculture improves adaptive capacity of cropping systems to climate stress in Malawi - Komarek, Adam M.; Thierfelder, Christian L.; Steward, Peter R. (Elsevier, 2021)
Context Adaptation to climate stress is an unprecedented challenge facing cropping systems. Most adaptation assessments focus on how adaptation options affect yields of a single crop under different weather or climate conditions. Yet, cropping systems often comprise more than one crop, and holistic assessments should consider all crops grown in a cropping system. One adaptation option is Conservation Agriculture that is commonly defined around a set of three principles: minimum mechanical soil disturbance, permanent soil organic cover, and crop species diversification.